An Interleukin-6 Receptor Antibody Suppresses Atherosclerosis in Atherogenic Mice - Akita, Koji; Isoda, Kikuo; Sato-Okabayashi, Yayoi; Kadoguchi, Tomoyasu; Kitamura, Kenichi; Ohtomo, Fumie; Shimada, Kazunori; Daida, Hiroyuki (Frontiers in Cardiovascular Medicine, 2017)
IkBNS is a nuclear IkB protein which negatively regulates nuclear factor-kB activity. We demonstrated that IκBNS deficiency accelerates atherosclerosis in LDL receptor-deficient (LDLr-/-) mice via increased IL-6 production by macrophages. Previous studies showed that the increase in IL-6 might contribute to the development of atherosclerotic lesions. However, whether an anti-mouse IL-6 receptor antibody (MR16-1) can protect atherosclerotic lesions in atherogenic mice remains to be elucidated. We investigated atherosclerotic lesions in LDLr-/- and IkBNS-/-/LDLr-/- mice after 16weeks consumption of a high-fat diet. All mice received intraperitoneal injections of MR16-1 or phosphate buffered saline (PBS) (control) once a week during a high-fat diet consumption. Treatment of MR16-1 yielded no adverse systemic effects, and we detected no significant differences in serum cholesterol levels in either group. The atherosclerotic lesions were significantly increased in IkBNS-/-/LDLr-/- compared with LDLr-/- mice (p<0.001) under treatment of PBS. However, MR16-1 treatment abolished the significant difference of atherosclerotic lesions between IkBNS-/-/LDLr-/- and LDLr-/- mice. Interestingly, MR16-1 also significantly decreased atherosclerotic lesions in LDLr-/- mice compared with PBS treatment (p<0.05). Immunostaining revealed percent phospho-STAT3-positive cell were significantly decreased in the atherosclerotic lesions of MR16-1 treated both IkBNS-/-/LDLr-/- and LDLr-/- mice compared with PBS treated mice, indicating MR16-1 could suppress atherosclerotic lesions via the inhibition of IL-6–STAT3 signaling pathway. This study highlights the potential therapeutic benefit of anti-IL-6 therapy in preventing atherogenesis induced by dyslipidemia and/or inflammation.